On-line Shopping Trends, Patterns and Preferences of University Undergraduate Students: A Survey Study on Sylhet Region - Rahaman , Md. Mahbubur (i-Proclaim, 2014)
With the explosion of the e-commerce in the past decade, different buying patterns and preferences have emerged for customer groups and other demographics. These patterns have been measured and collected by numerous independent marketing, business and even academic studies to understand how consumers connect with the new adventure of e-commerce. As the internet and online shopping is growing at a very fast pace worldwide, investigating this trend within Bangladeshi context is crucial considering that it is a relatively new trend in the country, the result is a lack of literature. This paper consists of the groundwork with a brief introduction of recent trends in e-commerce on people of Bangladesh; particularly its impact on university undergraduate students in Sylhet region. This has been followed by their general perceptions and preferences of the online shopping including products and website selection. Each of these e-commerce “characteristic” is compared to information combined from survey questions and open-ended discussions with a small sample group of university students at undergraduate level in Sylhet region. It also investigates into positive as well as negative website characteristics and sum up the favorable elements into a description of an e-commerce website that would suitable to the group being studied. Findings have been presented by means of the formation identified during the data analysis, indicated that an increasing number of the students at undergraduate level are now using the internet for purchase. It also observed that between male and female students, male students are purchasing products online more than female students. Although student’s participation is increasing, there are some limitations for what the potential numbers of students are not able to purchase via online. JEL Classification Code: A22; Z13